Perpetuation of H5N1 and H9N2 avian influenza viruses in natural water bodies - Zhang, Hongbo; Li, Yan; Chen, Jianjun; Chen, Quanjiao; Chen, Ze (Journal of general virology, 2014)
Water bodies are an important route for the spread and transmission of avian influenza virus (AIV). The determining factor for an AIV to transmit through diffusion in water is the term of viability of the virus in the water body. To better understand the perpetuation of AIV in natural water bodies, and thus the risks of AIV spread and transmission via such bodies, we systematically studied the inactivation dynamics of two AIV strains (H5N1 and H9N2) at different temperatures in water bodies of important migratory bird habitats within China (Dongting Lake, Poyang Lake, the Hubei segment of the Yangtze River and Qinghai Lake). We also studied the impact of water-borne micro-organisms on the perpetuation of AIV. Our findings indicated that water is very likely an important route for the epidemic spread of AIV, especially during the autumn and winter seasons. In addition, water-borne micro-organisms might antagonize the persistence of AIV.